Determinação da Atividade Anti-inflamatória e Antioxidante de Formulações Semissólidas Contendo Nanocápsulas de Nimesulida - Lenz, Quéli Fernandes (2009)
Non-steroidal anti-inflammatories (NSAIDs) represent one of the most commonly used classes of drugs, they are often applied in the treatment of chronic or acute inflammatory processes. Nimesulide, a drug which belongs to the NSAIDs, is usually applied in inflammatory processes, such as: inflammation of lower respiratory tract, oral cavity and in inflammatory processes associated to tendinitis, synovitis and rheumatoid arthritis. However, it is known that the oral administration of nimesulide might cause several adverse effects, from gastrointestinal disturbances to liver and kidney toxicity. Therefore, the topical administration of the drug is an alternative to these problems. Besides the use of such option, carriers ,such as nanoparticles, present many advantages for topic application. Among them, the sustained liberation, which becomes important for the drug supply on the skin during a longer period of time. This work aims at assessing the anti-inflammatory and the antioxidant activity of a topical gel containing nanoencapsulated nimesulide by using experimental models, as well as carrying out comparative analysis related to the nimesulide activity either free or nanostructured. In order to determine the anti-inflammatory activity, either acute or chronic, male rats were used Wistar (200 e 250g). In order to evaluate the acute inflammation, paw edema induced by carrageenan and acute arthritis inductions by Freud Adjuvant were used. The chronic inflammation models in vivo applied were induction of chronic arthritis by Freud Adjuvant, induction of formation of granulomatous tissue by cotton pellet and healing. The antioxidant activity was assessed through radical capturing method DPPH and dosage of substances reactive to the tiobarbituric acid (TBARS) in dorsal damaged tissue (healing model). The nanocapsules of nimesulide (1,5 mg/ml) were prepared through the method of nanoprecipitation of preformed polymer (Fessi, et al. 1998), developed and characterized by Alves and collaborators (2005). From the obtained data in the acute inflammation models, no significative difference was observed between the activity of the nimesulide in nanocapsules (GHNCN) and in the free form (GHN), where both the formulations were able to inhibit the inflammatory process. On the other hand, in the chronic inflammation the formulation containing the nonostructured drug showed a better activity than that showed by the free drug. In the chronic arthritis model the anti-inflammatory activity was 81,5%, compared to the free drug (27,75%). The formulation containing the nanostructured drug was also able to inhibit the formation of granulomatous tissue in 36,66% compared to the free drug, which inhibited just 2,82. In the healing trial the free drug (GHN) presented an tissue retraction of 38,82%, the nanostructured of 19,35% and the control of 10,5%. Through the DPPH technique, it was not possible to observe any significant difference between the formulations (GHNCN e GHN), however, both demonstrated excellent antioxidant action. Although not statistically different, it was possible to observe a higher action in the formulation containing nimesulide in nanocapsules in all tested concentrations. In the determination of TBARS malondialdehyde levels (MDA) for the free and the nanostructured drugs were respectively 730,20 e 571,33 nmol MDA/g tissue, compared to the control group (1.457 nmol MDA/g tissue). From the obtained data, it was possible to demonstrate that the nanostructured nimesulide incorporated to the hydro gel presents adequate anti-inflammatory and antioxidant activities, becoming an alternative to the treatment of inflammatory processes through topical administration.